Thomas Holcroft's revolutionary drama : reception and afterlives - Garnai, Amy, 1957- (Transits: Literature, Thought and Culture, 1650-1850 Ser., 2023)
A key figure in British literary circles following the French Revolution, novelist and playwright Thomas Holcroft promoted ideas of reform and equality informed by the philosophy of his close friend William Godwin. Arrested for treason in 1794 and released without trial, Holcroft was notorious in his own time, but today appears mainly as a supporting character in studies of 1790s literary activism. Thomas Holcroft's Revolutionary Drama authoritatively reintroduces and reestablishes this central figure of the revolutionary decade by examining his life, plays, memoirs, and personal correspondence. In engaging with theatrical censorship, apostacy, and the response of audiences and critics to radical drama, this thoughtful study also demonstrates how theater functions in times of political repression. Despite his struggles, Holcroft also had major successes: this book examines his surprisingly robust afterlife, as his plays, especially The Road to Ruin, were repeatedly revived worldwide in the nineteenth century.